Sustained Health Care–Associated Infection Reduction Among Electronic Hand Hygiene Monitoring System Clients - Gabrielle Genovesi (Interactive Journal of Medical Research, 2026)
Abstract This multifacility retrospective analysis of 25 hospitals using BioVigil Technologies’ electronic hand hygiene monitoring system demonstrated a mean of 46.95% (95% CI 35.5%‐58.4%) sustained reductions in health care–associated infections in 2024 compared to pre-implementation baselines, highlighting the clinical and operational value of automated hand hygiene monitoring at scale.